Different ways for visualization of data obtained from an arduino uno microcontroller board - Pavlov-Kagadejev Marijana (Mining and Metallurgy Engineering Bor, 2021)
Arduino microcontroller platforms are frequently in use in the last few years. The reason is their simplicity, low cost, and availability of a large number of ready-made solutions on the Internet. The Arduino Integrated Development Environment itself has a Serial Monitor and Serial Plotter tools for data presentation. The Serial Monitor displays the textual and numeric values of the data obtained through the serial port. By using the Serial Plotter, measurement results from the Arduino serial port can be seen in the form of Real-Time diagrams. The deficiency of such a way of data visualization is that it does not provide many opportunities for change and adaptation to the user needs. This paper presents examples of several different programming environments which provide the good opportunities for presentation the results generated by the Arduino boards. Some hardware modules used to display data from the Arduino boards are also described in this paper.